Tergerusnya Eko-Populisme Pengelolaan Lahan Gambut: Dampak Program Food Estate di Desa Bentuk Jaya Kabupaten Kapuas - Devi Permata Putri; Ismar Hamid (Huma: Jurnal Sosiologi, 2023)
Peatlands with the characteristics that are prone to ecological damage, and the eco-populism of peatland management, are under threat due to the food estate program. The purpose of this study is to determine the impact of the food estate program on eco-populist values in peatland management in Bentuk Jaya Village Kapuas Regency. The research approach used is a qualitative approach with a case study type. Data were collected through participant observation, in-depth interviews and documentation. The results of this study show the ineffectiveness of the food estate program in Bentuk Jaya Village, especially in the agricultural sector. The results obtained have not been able to reach the target due to crop failure. The agricultural system that is applied not in accordance with the environmental conditions of peat is the root of the problem. In addition, the implementation of the food estate program ignores the eco-populist values of peatland management that exist in the community. Eco-populism is a perspective that pays more attention to the fate of people whose sources of life come from nature. A perspective that is contrary to the reality of the food estate program in Bentuk Jaya Village. The existence of the food estate program has an impact on the erosion of local wisdom of the community in farming, changes in the carrying capacity of the peat environment on people's lives, and the loss of community sources of life from endemic plants of peat ecosystems. Communities before the existence of food estate managed and utilized natural products in a way that adapted to peatland environmental conditions and was based on local wisdom. Now inversely, programs designed to prosper the community and oriented towards supporting the fulfillment of food needs nationally actually have a negative impact on the environment and society.